PROJETO “CÂMARA ESCURA: HISTÓRIAS E PRÁTICAS FOTOGRÁFICAS” - Noll, Gerson A. G. C.; Mello, Kassieli J. G. d.; Scortegagna, Paulo E.; Stefanello, Belair; Karnikowski, Ulisses S.; Binicheski, Jonas B.; Atkinson, Gerson; Provenci, Janaina; Santi, Mirian (Salão do Conhecimento, 2013)
Resumo